Strawberry gingivitis as the first presenting sign of Wegener's granulomatosis: report of a case - Siar, C.H.; Yeo, K.B.; Nakano, K.; Nagatsuka, H.; Tsujigiwa, H.; Tomida, M.; Ng, K.H.; Kawakami, T. (2011)
Wegener's granulomatosis is a rare multi-system disease characterized by the classic triad of necrotizing granulomas affecting the upper and lower respiratory tracts, disseminated vasculitis and glomerulonephritis. Oral lesions as a presenting feature are only encountered in 2 of these cases. Hyperplastic gingival lesions or strawberry gingivitis, is a characteristic sign of Wegener's granulomatosis. The latter consists of reddish-purple exophytic gingival swellings with petechial haemorrhages thus resembling strawberries. Recognition of this feature is of utmost importance for timely diagnosis and definitive management of this potentially fatal disease. A case of strawberry gingivitis as the first presenting sign of Wegener's granulomatosis affecting a 50-year-old Malay male is reported here. The differential diagnosis of red lesions that may present in the gingiva is discussed.